2012
DOI: 10.1186/1471-2296-13-49
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions in primary care to improve health literacy for chronic disease behavioral risk factors

Abstract: BackgroundTo evaluate the effectiveness of interventions used in primary care to improve health literacy for change in smoking, nutrition, alcohol, physical activity and weight (SNAPW).MethodsA systematic review of intervention studies that included outcomes for health literacy and SNAPW behavioral risk behaviors implemented in primary care settings.We searched the Cochrane Library, Johanna Briggs Institute, Medline, Embase, CINAHL, Psychinfo, Web of Science, Scopus, APAIS, Australasian Medical Index, Google S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
154
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(169 citation statements)
references
References 51 publications
4
154
2
9
Order By: Relevance
“…A systematic review of 52 primary care health literacy interventions found that 73 % were associated with health literacy improvements. 28 Clinics might also provide community health education events, like health fairs, to reach people beyond the traditional patient encounter. Innovative examples exist for improving community social determinants in the context of primary care.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 52 primary care health literacy interventions found that 73 % were associated with health literacy improvements. 28 Clinics might also provide community health education events, like health fairs, to reach people beyond the traditional patient encounter. Innovative examples exist for improving community social determinants in the context of primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Bevölkerungs-gruppen mit besonders geringer GK sind häufig durch einen niedrigen Bildungsstand, geringes Einkommen, einen Migrationshintergrund, einen schlechten Gesundheitszustand und ein hohes Lebensalter gekennzeichnet [2,10,[14][15][16]. Daher werden zunehmend Interventionen zur Verbesserung der GK entwickelt, besonders für Patientinnen und Patienten in der Gesundheitsversorgung [17,18], aber auch für Bevölkerungsgruppen mit spezifischen Risiken oder Erkrankungen [13,[19][20][21]. Folglich nimmt auch der Bedarf an der Erhebung und Ermittlung der individuellen GK und insbesondere der Verteilung der GK in der Bevölkerung zu.…”
Section: "Gesundheitskompetenz Ist Mit Der Leseund Schreibfähigkeit Vunclassified
“…Although health literacy may not be easily and sustainably modifiable, literacy-level-appropriate interventions may be effective. Possible strategies could include healthliteracy-modulating approaches such as motivational interviewing, group counseling, peer support, outreach workers, and improved print and visual materials (Kaakko et al, 2002;Taggart et al, 2012). To mention one possible interventional avenue, the WIC program (9.2 million participants in the USA in fiscal year 2010) has always had a strong interest in oral health, and it offers both the logistical capacity and caregiver access for staging a health-literacy-appropriate intervention.…”
mentioning
confidence: 99%